2018
DOI: 10.1038/pr.2018.2
|View full text |Cite
|
Sign up to set email alerts
|

Severe retinopathy of prematurity is associated with reduced cerebellar and brainstem volumes at term and neurodevelopmental deficits at 2 years

Abstract: BackgroundTo evaluate the association between severe retinopathy of prematurity (ROP), measures of brain morphology at term-equivalent age (TEA), and neurodevelopmental outcome.MethodsEighteen infants with severe ROP (median gestational age (GA) 25.3 (range 24.6-25.9 weeks) were included in this retrospective case-control study. Each infant was matched to two extremely preterm control infants (n=36) by GA, birth weight, sex, and brain injury. T2-weighted images were obtained on a 3 T magnetic resonance imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 38 publications
2
27
0
Order By: Relevance
“… Sveinsdóttir et al (2018) showed a relation between ROP and lower cerebellar volume and lower unmyelinated white matter volume at TEA. Moreover, Drost et al (2018) showed an association between severe ROP and reduced cerebellar and brainstem volumes measured by automatic segmentation method at TEA. Both of those studies concluded to neurodevelopmental deficits at 2 years ( Drost et al, 2018 ; Sveinsdóttir et al, 2018 ).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“… Sveinsdóttir et al (2018) showed a relation between ROP and lower cerebellar volume and lower unmyelinated white matter volume at TEA. Moreover, Drost et al (2018) showed an association between severe ROP and reduced cerebellar and brainstem volumes measured by automatic segmentation method at TEA. Both of those studies concluded to neurodevelopmental deficits at 2 years ( Drost et al, 2018 ; Sveinsdóttir et al, 2018 ).…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, Drost et al (2018) showed an association between severe ROP and reduced cerebellar and brainstem volumes measured by automatic segmentation method at TEA. Both of those studies concluded to neurodevelopmental deficits at 2 years ( Drost et al, 2018 ; Sveinsdóttir et al, 2018 ). For medical teams that do not have these measurement techniques available, VSA is an easy to measure indicator in routine MRI.…”
Section: Discussionmentioning
confidence: 86%
“…In this cohort, we observed an independent association of systemic infection and NEC with several metabolic alterations in the developing cerebellum in the early postnatal period. Decreased white matter and cerebellar volumes on quantitative MRI has been reported in infants with any stage of ROP 40,41 but MR spectroscopic alterations are unknown. In our study, infants with ROP (stage 2 or higher) had lower NAA and Cr concentrations compared to those without ROP although the relationship lost statistical significance after adjusting for co-variates.…”
Section: Discussionmentioning
confidence: 98%
“…Fetal growth restriction (FGR) complicates 5–10% of pregnancies and is associated with increased risks of perinatal morbidity and mortality (Bernstein et al., 2000). FGR is linked to adverse perinatal outcomes, including stillbirth, prematurity, and need for neonatal intensive care; as well as long-term adverse outcomes including metabolic syndromes, hypertension, and neurological deficits (Baschat, 2011; Mayer and Joseph, 2013; Albu et al., 2014; Drost et al., 2018). FGR is principally caused by placental insufficiency, which results in reduced utero-placental transfer of oxygen and nutrients to the developing fetus (Figueras and Gardosi, 2011).…”
Section: Introductionmentioning
confidence: 99%